Shahnama studies III : the reception of the Shahnama - Van den Berg, Gabrielle Rachel, 1967-; Melville, C. P. 1951- (Studies in Persian Cultural History, 2018)
Shahnama Studies III focuses on the hugely successful afterlife of the Shahnama or Book of Kings, completed by the poet Firdausi around 1010 AD. This long epic grew out to be an icon of Persian culture and served as a source of inspiration for art and literature, leaving its traces in manifold ways. The contributors to this volume each treat an aspect of the rich legacy of the Shahnama and offer new insights in Shahnama manuscript studies, the illustration of the Shahnama , the phenomenon of later epics, and the Shahnama in later texts and contexts.